Potential Cognitive Benefits From Playing Music Among Cognitively Intact Older Adults: A Scoping Review. (December 2019) - Schneider, Catherine E.; Hunter, Elizabeth G.; Bardach, Shoshana H.
The aging population is growing rapidly, raising rates of cognitive impairment, which makes strategies for protection against cognitive impairment increasingly important. There is little evidence indicating highly effective interventions preventing or slowing onset of cognitive impairment. Music playing influences brain and cognitive function, activating multiple brain areas and using cognitive and motor functions as well as multiple sensory systems, simultaneously. The purpose of this study was to review the current evidence related to playing a musical instrument being a potentially protective mechanism against cognitive decline among older adults. Using scoping review procedures, four databases were searched. Paired reviewers analyzed articles for content, design, and bias. Eleven studies met study criteria and were included in the review. All studies showed that music playing was correlated with positive outcomes on cognitive ability; more high-quality research is needed in this area to understand mechanisms behind potential cognitive protection of music.